2018
DOI: 10.22201/cgeo.20072902e.2018.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and isotopic signatures of hot springs from east-central Sonora State, Mexico: a new prospection survey of promissory low-to-medium temperature geothermal systems

Abstract: A promissory low-to-medium temperature geothermal system located in Sonora (Mexico) has been studied. In the present work, a detailed geochemical survey was carried out to understand the hydrogeochemical signatures of hot spring waters. A field work campaign was conducted for collecting water samples from twelve hot springs placed in four major zones (NW, NE, C, and S). The collected samples were analysed by chemical and isotopic methods for determining their chemical (major and trace elements) and isotopic (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 51 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Table 1 summarizes the precision and accuracy errors (in %) reported for the chemical analyses, including the limits of detection (LODs), for each one of the elements. Accuracy was evaluated by analyzing water-certified standards as external testers [18]. The ion charge imbalances for the water samples were calculated using the program AquaChem, and the results showed that all of the geothermal water samples have a charge imbalance less than ±3%, while most of the cold water samples have a charge imbalance more than ±10%, as the concentration is too low which leads to a larger error in the detection.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarizes the precision and accuracy errors (in %) reported for the chemical analyses, including the limits of detection (LODs), for each one of the elements. Accuracy was evaluated by analyzing water-certified standards as external testers [18]. The ion charge imbalances for the water samples were calculated using the program AquaChem, and the results showed that all of the geothermal water samples have a charge imbalance less than ±3%, while most of the cold water samples have a charge imbalance more than ±10%, as the concentration is too low which leads to a larger error in the detection.…”
Section: Methodsmentioning
confidence: 99%